APLIKASI SISTEM PAKAR BERBASIS WEB UNTUK MENDIAGNOSA PENYAKIT MENULAR SEKSUAL DENGAN METODE FUZZY LOGIC - Wira Apriani (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
Sexually transmitted diseases are diseases that attack humans and animals. Patients with sexually transmitted diseases in areas or cities continue to grow every year. At present the community has difficulty in knowing the symptoms or facts that are included in sexually transmitted diseases. Based on these problems, a software is designed to solve problems related to the diagnosis of sexually transmitted diseases by applying the fuzzy logic method. The programming languages used in the design of expert systems are PHP and Mysql databases. So it is hoped that the system can help the public to diagnose PMS easily and accurately